Strategi Pemasaran Pupuk Dolomit Di PT. Magnesium Gosari Internasional - Radjasa, Rifqy Ahnand; Djazuli, Raden Achmad (Jurnal Ekonomi Pertanian dan Agribisnis, 2024)
The purpose of this research is to analyze the marketing strategy implemented by PT. Magnesium Gosari International in promoting its dolomite fertilizer products. Qualitative methods were used in this research, which involved collecting data through observation, interviews and literature reviews. The research results show that PT. Magnesium Gosari International uses a direct marketing strategy, conducting face-to-face interactions with potential consumers (direct selling) and utilizing communication tools such as email, letters and telephone. The company implements a segmentation strategy based on geography and behavior, targeting farmer groups and business actors in the agricultural, plantation and industrial sectors. The company's positioning is focused on the production of high quality dolomite fertilizer products to meet domestic and international needs. The marketing mix consists of various brands and types of dolomite fertilizer products, flexible prices, online and offline promotional activities, and efficient distribution channels. Challenges faced include losing tenders due to uncompetitive transportation costs, incomplete distribution coverage throughout Indonesia, and limited awareness of farmers regarding the benefits of dolomite fertilizer.